The Coimbra Workshop in Musculoskeletal Stress Markers (MSM): an annotated review - Santos, Ana Luísa (2011)
The Workshop in Musculoskeletal Stress Markers (MSM): limitations and achievements in the reconstruction of past activity patterns, was held at the University of Coimbra, in Portugal (2nd – 3rd July 2009). The chief goal of the organizing committee was to provide a productive environment where researchers could discuss the methodologies and terminology employed for the study of MSM as well as assessing how well these enthesopathies serve as markers of occupational stress. The Workshop was organized in three major sessions, each one introduced by a keynote lecture: (1) Methodological issues; (2) MSM studies of archaeological samples and Identified Skeletal Collections; and (3) The multifactorial etiology of enthesopathies. The meeting was concluded with a Plenary Session where two annotators discussed the presentations; this was followed by a general discussion and the formation of three working groups focused on the topics of Methods, Terminology, and Occupations. Details of the Workshop and the presentations presented are available for download at http://www.uc.pt/en/cia/msm/. A blog (http://coimbraworkshopmsm.blogspot. com/) was created to facilitate communications about individual experiences and to share knowledge among researchers in this field. We hope that this Workshop will help to standardize methodologies and terminology and promote the creation of a more integrated scientific approach to future studies of MSM.